2015
DOI: 10.1016/j.bmcl.2015.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of constrained phosphoramidate inhibitors of prostate-specific membrane antigen

Abstract: Prostate-specific membrane antigen (PSMA) is a cell-surface enzyme-biomarker that is actively pursued for targeted delivery of imaging and therapeutic agents for prostate cancer. Our lab has developed PSMA inhibitors based on a phosphoramidate scaffold, which has shown both high selectivity for PSMA-positive tumors and rapid clearance in vivo when radiolabeled with (18)F. However, this scaffold exhibits hydrolytic instability under low pH and high temperature conditions, barring the use of other imaging or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Rate constants were extracted from GraphPad Prism 9.0 by fitting the data to one phase association model. recently described in our laboratory, 62 using concentrations of 100, 30, 10, 3, and 1 nM. 4.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rate constants were extracted from GraphPad Prism 9.0 by fitting the data to one phase association model. recently described in our laboratory, 62 using concentrations of 100, 30, 10, 3, and 1 nM. 4.5.…”
Section: Methodsmentioning
confidence: 99%
“…The routine determination of IC 50 for Coum-SMDC was performed, as most recently described in our laboratory, using concentrations of 100, 30, 10, 3, and 1 nM.…”
Section: Methodsmentioning
confidence: 99%
“…Further development included the introduction of substances with a phosphinic or phosphonate core by Jackson et al [44] and the development of phosphoramidate compounds by Berkman et al [45,46], with promising results for clinical applications; therefore, the phosphoamidate-derived inhibitor was used in the first phosphorous-based PSMA-targeting LMW molecule for 18 F-PET imaging [47]. Additionally, in the development of further tracers of this class, the described binding entity served as a basic structure for numerous new radiopharmaceuticals [48][49][50][51][52][53]. With promising results in a phase I clinical study, the PSMA tracer CTT1057 showed great potential as a novel candidate for further clinical testing [53].…”
Section: Binding Entitymentioning
confidence: 99%
“…To date, a variety of urea-based PSMA inhibitors have been developed and labeled with different SPECT ( 99m Tc, 111 In), PET ( 68 Ga, 64 Cu), and therapeutic ( 177 Lu) radiometals using several chelators and showed great promise not only preclinicaly but also in the clinical assessment. Apart from the radiometals to be used as the cytotoxic units, a considerable amount of urea-based PSMA inhibitors labeled with 11 C, 125 I, 124 I, 131 I and 18 F, have also been reported [ 19 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. These radiotracers were also able to successfully image PSMA-expressing xenografted mice, but since this is beyond the focus of this review no further information will be given here with regard to this topic.…”
Section: Urea-based Psma Inhibitorsmentioning
confidence: 99%